Spherical detector device mathematical modeling with taking into account detector module symmetry - Batiy, V.G.; Fedorchenko, D.V.; Prokhorets, I.M.; Prokhorets, S.I.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2005)
Mathematical model for spherical detector device accounting to symmetry properties is considered. Exact algorithm for simulation of measurements procedure with multiple radiation sources developed. Modelling results are shown to have perfect agreement with calibration measurements